Preparation method and application of scandium-aluminum-oxygen high-k gate dielectric film

By using scandium aluminum oxygen high-k gate dielectric film in TFT devices, the problem of insufficient mobility and capacitance per unit area of ​​existing TFT devices is solved, efficient capacitance and low power consumption are achieved, and the thermal stability and reliability of the device are improved.

CN119776787AActive Publication Date: 2025-04-08INST OF MATERIALS HENAN ACAD OF SCI +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411977131.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-08
Estimated Expiration
2044-12-31

AI Technical Summary

Technical Problem

Existing TFT devices have limitations in improving mobility and capacitance per unit area, resulting in insufficient driving current, high working voltage and large power consumption. At the same time, high-k gate dielectric materials have problems such as narrow band gap, insufficient withstand voltage strength and easy crystallization.

Method used

Scandium aluminum oxygen high-k gate dielectric film was used to adjust the Sc/Al molar ratio in the ceramic target by magnetron sputtering method, and a 100nm-thick Sc-Al-O gate dielectric film was prepared, and annealed at 300°C to 500°C to obtain a dense material.

Benefits of technology

It achieves high k value (12.4), high capacitance per unit area (550nF/cm2) and high optical transmittance (≥96%), while improving the gate control capability of the TFT device, reducing operating voltage and power consumption, and enhancing thermal stability and reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119776787A_ABST
    Figure CN119776787A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a scandium-aluminum-oxygen high-k gate dielectric film, and the method comprises the steps: cleaning a glass substrate or a Si substrate, and sequentially carrying out the ultrasonic cleaning of the glass substrate or the Si substrate in acetone, alcohol and deionized water for 20 minutes, so as to remove impurities on a substrate; blow-drying the cleaned substrate by using nitrogen, and drying the substrate in a drying oven at 100 DEG C for 10 minutes; the method comprises the following steps: preparing an Sc-Al-O gate dielectric film with the thickness of 100nm on a film substrate by using an Sc-Al-O ceramic target material through a magnetron sputtering method; the prepared Sc-Al-O thin film is annealed for 0.5 h-2 h at the temperature of 300 DEG C-500 DEG C under the condition of air or oxygen in a tubular furnace, and a compact gate dielectric material is obtained; the Sc-Al-O gate dielectric provided by the invention not only can effectively restrain a carrier tunneling effect caused by thinning of the gate dielectric and reduce heat loss, but also can improve the gate control capability of a TFT (Thin Film Transistor) device and reduce the working voltage of the TFT device, thereby further reducing the power consumption of the device and improving the reliability of the device. The method is of great significance to application of ultra-low power consumption display technologies such as wearable equipment and electronic paper.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of microelectronics and integrated circuits, and specifically relates to a gate dielectric material in a thin film transistor (TFT) device, which is a core basic unit of a flat panel display backplane, and in particular to a novel composite high-k gate dielectric film and a preparation method and application thereof. Background Art

[0002] Thin-film transistors (TFTs), as a kind of miniature electronic switching devices, are mainly used in the field of flat-panel displays. They are the core components of pixel circuits and also show great application prospects in the field of sensors. With the rapid development of information display technology, higher requirements are placed on TFT devices. In order to meet the display requirements of large size, ultra-high resolution and high frame rate, it is required to have higher driving capability, which in turn requires improving the mobility of the active layer or the unit area capacitance of the gate dielectric. At present, the research on high mobility is relatively extensive, but the improvement of mobility is very limited and is usually accompanied by the problem of deteriorated stability. Increasing the unit area capacitance of the gate dielectric is more feasible, but it has not attracted enough attention. It can not only significantly increase the driving current of the TFT device, but also effectively reduce the operating voltage and power consumption of the TFT device. Increasing the unit area capacitance of the gate dielectric requires reducing the thickness of the gate dielectric or using a high-k gate dielectric. For the current mainstream SiO 2 For low-k gate dielectrics, although reducing the thickness can indeed improve the gate control ability of TFT devices, when the gate dielectric is thinned to a certain extent, it will cause unacceptable leakage current, heat loss and stability problems. The use of high-k gate dielectrics can not only improve the performance of TFT devices and reduce their power consumption, but also effectively solve the leakage problem caused by the thinning of the gate dielectric. Although there have been some reports on high-k gate dielectric materials, such as HfO 2 , Y 2 O 3 、 2 O 5 However, most of these materials face problems such as narrow band gap, insufficient voltage resistance, and easy crystallization. Therefore, the development of new high-k gate dielectric materials is of great significance to promote the new generation of TFT backplane technology and its industry. Summary of the invention

[0003] In order to solve the above technical problems, the present invention provides a technical solution: a method for preparing a scandium aluminum oxide high-k gate dielectric film, comprising the following steps:

[0004] S1. Clean the glass substrate or Si substrate by ultrasonic cleaning in acetone, alcohol, and deionized water for 20 minutes to remove impurities on the substrate;

[0005] S2, blowing the cleaned substrate dry with nitrogen, and drying it in an oven at 100° C. for 10 minutes;

[0006] S3, using a Sc-Al-O ceramic target to prepare a 100 nm thick Sc-Al-O gate dielectric film on a film substrate by a magnetron sputtering method, wherein the Sc / Al molar ratio of the Sc-Al-O ceramic target is in the range of 0.8 to 1.2;

[0007] S4. Annealing the prepared Sc-Al-O film in a tube furnace under air or oxygen conditions at 300° C. to 500° C. for 0.5 h to 2 h to obtain a dense gate dielectric material.

[0008] Preferably, in step S3, the molar ratio of Sc / Al is preferably 1, denoted as ScAlO x The specific deposition conditions are local vacuum 5×10 -4 Pa, DC sputtering power 100W ~ 160W, working pressure 0.3Pa ~ 0.6Pa, sputtering atmosphere Ar / O 2 =50 / 0sccm~25sccm / 25sccm.

[0009] Preferably, the ScAlO obtained in step S4 is further included x The electrical properties of the material are tested, including the following:

[0010] S5. In order to directly test the electrical properties of the gate dielectric material, a 100 nm thick and patterned metal Al layer is deposited on the above film as an electrode by magnetron sputtering combined with a shadow mask method.

[0011] Preferably, the deposition conditions of step S5 are: local vacuum 5×10 -4 Pa, DC sputtering power 120W, working gas pressure 0.4Pa, sputtering atmosphere is pure Ar = 50sccm.

[0012] Preferably, the ScAlO obtained in step S4 is further included x The effectiveness of the TFT gate dielectric layer is tested, including the following:

[0013] S6. Obtain high-density ScAlO in step S4 x A TFT device is prepared based on the material; specifically, a patterned InGaZnO (IGZO) semiconductor film is prepared as a channel layer of the TFT device by a method of magnetron sputtering combined with a shadow mask;

[0014] S7, annealing the prepared IGZO film in a tube furnace at 300° C. to 400° C. for 0.5 h to 2 h in air or oxygen conditions to obtain a channel layer material with a low defect density;

[0015] S8, depositing a 100 nm thick metal Al layer as an electrode on the IGZO film by using a magnetron sputtering combined with a shadow mask method;

[0016] S9. Cut the gate dielectric layer at the edge to expose the underlying Si substrate serving as the gate for subsequent device performance testing.

[0017] Preferably, in step S6, the mass ratio of each component in the IGZO semiconductor film is In:Ga:Zn=1:1:1; and the deposition conditions are: local vacuum 5×10 -4 Pa, DC sputtering power 120W, working pressure 0.5Pa, sputtering atmosphere Ar / O 2 =46sccm / 4sccm.

[0018] The invention also discloses the application of the scandium aluminum oxide high-k gate dielectric film in a thin film transistor.

[0019] The advantages of the present invention compared with the prior art are:

[0020] (1) Compared with the currently mainstream SiO 2 Compared with the gate dielectric, the ScAlO x The gate dielectric has a higher k value (12.4) and a higher gate capacitance per unit area (550nF / cm 2 ), a higher dielectric layer equivalent thickness (6.5nm), so it can not only effectively suppress the carrier tunneling effect caused by gate dielectric thinning and reduce heat loss, but also improve the gate control ability of TFT devices and reduce the operating voltage of TFT devices, thereby further reducing device power consumption, which is of great significance for the application of ultra-low power display technologies such as wearable devices and electronic paper.

[0021] (2) The ScAlO x The grating medium has an ultra-high optical transmittance (≥96%) in the visible light range and has high application value in transparent display, augmented reality fusion, etc.

[0022] (3) With HfO 2 Compared with other high-k gate dielectric materials, ScAlO x The gate dielectric has a high bandgap (5.6eV), which can effectively suppress the thermal migration of carriers, thereby improving the thermal stability and reliability of TFT devices. In addition, due to the increase in oxide components, the leakage problem caused by the easy crystallization of simple oxides can be effectively avoided.

[0023] (4) The film prepared by this method has a high surface flatness, with a surface roughness of only 0.8 nm, which is conducive to the rapid transport of carriers.

[0024] (5) The IGZO TFT device based on this gate dielectric has normal transfer characteristics and output characteristic curves, and its mobility, threshold voltage, subthreshold swing and on-off ratio are 7.2 cm 2 / Vs, 1V, 67mV / dec and 10 7 The device has high working stability. After 2000s of gate voltage stress of +2V and -2V, the threshold voltage drift is no more than 0.71V and -0.63V respectively.

[0025] In summary, the ScAlO x Gate dielectric is a new type of high-k gate dielectric material with great application potential. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 The results of (a) optical transmittance and optical bandgap extraction, (b) current density, (c) capacitance per unit area and (d) surface roughness of the ScAlOx gate dielectric film in the present invention.

[0027] Figure 2 (a) transfer characteristic curve, (b) output characteristic curve, (c) positive bias stability and (d) negative bias stability results of the IGZO TFT device based on 20nm ScAlOx high-k gate dielectric in the present invention. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0029] In the description of the embodiments of the present invention, it should be noted that if the terms "center", "upper", "lower", "left", "right", "vertical", "horizontal", "inner", "outer", etc. appear, the orientation or position relationship indicated is based on the orientation or position relationship shown in the drawings, or the orientation or position relationship in which the invented product is usually placed when used. It is only for the convenience of describing the present invention and simplifying the description, and does not indicate or imply that the device or element referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore cannot be understood as a limitation on the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0030] In addition, the terms "horizontal", "vertical", "overhanging" and the like do not mean that the components must be absolutely horizontal or overhanging, but can be slightly tilted. For example, "horizontal" only means that its direction is more horizontal than "vertical", and does not mean that the structure must be completely horizontal, but can be slightly tilted.

[0031] In the description of the embodiments of the present invention, "plurality" means at least 2.

[0032] In the description of the embodiments of the present invention, it is also necessary to explain that, unless otherwise clearly specified and limited, the terms "set", "install", "connect", and "connect" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection, or it can be indirectly connected through an intermediate medium, or it can be the internal connection of two components. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.

[0033] Example:

[0034] Combined with Figure 1-2 The present embodiment provides a method for preparing a scandium aluminum oxide high-k gate dielectric film, comprising the following steps:

[0035] S1. Clean the glass substrate or Si substrate by ultrasonic cleaning in acetone, alcohol, and deionized water for 20 minutes to remove impurities on the substrate;

[0036] S2, blowing the cleaned substrate dry with nitrogen, and drying it in an oven at 100° C. for 10 minutes;

[0037] S3, using a Sc-Al-O ceramic target to prepare a 100 nm thick Sc-Al-O gate dielectric film on a film substrate by a magnetron sputtering method, wherein the Sc / Al molar ratio of the Sc-Al-O ceramic target is in the range of 0.8 to 1.2; the Sc / Al molar ratio is preferably 1, which is denoted as ScAlO x The specific deposition conditions are local vacuum 5×10 -4 Pa, DC sputtering power 100W ~ 160W, working pressure 0.3Pa ~ 0.6Pa, sputtering atmosphere Ar / O 2 =50 / 0sccm~25sccm / 25sccm.

[0038] S4, the ScAlO prepared above x The film is annealed in air or oxygen in a tube furnace at 300° C. to 500° C. for 0.5 h to 2 h to obtain a dense gate dielectric material;

[0039] S5. In order to directly test the electrical properties of the gate dielectric material, a 100 nm thick and patterned metal Al layer was deposited on the above film by magnetron sputtering combined with a shadow mask as an electrode. The deposition conditions were: local vacuum 5×10 -4 Pa, DC sputtering power 120W, working gas pressure 0.4Pa, sputtering atmosphere pure Ar = 50sccm;

[0040] S6, the ScAlO obtained in step S4 x Test the effectiveness as a TFT gate dielectric layer: In step S4, a high-density ScAlO x The TFT device is prepared based on the material; specifically, a patterned IGZO semiconductor film is prepared as the channel layer of the TFT device by a method of magnetron sputtering combined with a shadow mask; the mass ratio of each component in the IGZO semiconductor film is In:Ga:Zn=1:1:1; its deposition conditions are: local vacuum 5×10 -4 Pa, DC sputtering power 120W, working pressure 0.5Pa, sputtering atmosphere Ar / O 2 =46sccm / 4sccm.

[0041] S7, annealing the prepared IGZO film in a tube furnace at 300° C. to 400° C. for 0.5 h to 2 h in air or oxygen conditions to obtain a channel layer material with a low defect density;

[0042] S8, depositing a 100 nm thick metal Al layer as an electrode on the IGZO film by using a magnetron sputtering combined with a shadow mask method;

[0043] S9, cutting the gate dielectric layer at the edge to expose the underlying Si substrate serving as the gate for subsequent device performance testing;

[0044] In the accompanying drawings, Figure 1 As shown:

[0045] Figure 1 (a) ScAlO prepared under different conditions x The optical transmittance of the films shows that in the visible light range, all the films have very high transmittance (≥96%) and the optical band gap is between 4.5 and 5.6 eV. 2 With the increase of content, the band gap gradually increases.

[0046] from Figure 1 It can be seen from the leakage current curve in (b) that with the increase of oxygen content in the sputtering atmosphere, ScAlO x The leakage current of the gate dielectric film is generally decreasing, and the maximum withstand voltage is about 4.4MV / cm.

[0047] from Figure 1 From the CV curve in (c), the 20nm thick ScAlO x Gate dielectric C ox About 550nF / cm 2 , EOT is about 6.5nm, and k value is about 12.4.

[0048] Finally from Figure 1 From the AFM image in (d), ScAlO x The surface flatness of the gate dielectric film is relatively high, with a root mean square roughness of only 0.8nm.

[0049] like Figure 2 As shown:

[0050] (1) From the transfer characteristic curve, the 20nm ScAlO x The IGZO TFT with thin film as gate dielectric exhibits good device switching characteristics, with low off-state current at the order of 10pA and an on-off ratio of 10 7 , the threshold voltage is around 1V, and it also has an ultra-low subthreshold swing (67mV / dec);

[0051] (2) From the output characteristic curve, the device still exhibits excellent gate control capability even at a relatively low gate voltage, and no obvious current crowding phenomenon is observed;

[0052] (3) In terms of positive / negative bias stability, the device has good stability under 2000s and ±2V gate bias stress, and the threshold voltage drift is less than 0.7V.

[0053] The present invention and its embodiments are described above, and such description is not restrictive. The drawings show only one embodiment of the present invention, and the actual structure is not limited thereto. In short, if ordinary technicians in the field are inspired by it and design structural methods and embodiments similar to the technical solution without creativity without departing from the purpose of the invention, they should all fall within the protection scope of the present invention.

Claims

1. A method for preparing a scandium aluminum oxide high-k gate dielectric film, characterized in that: The following steps are involved: S1. Clean the glass substrate or Si substrate by ultrasonic cleaning in acetone, alcohol, and deionized water for 20 minutes to remove impurities on the substrate; S2, blowing the cleaned substrate dry with nitrogen, and drying it in an oven at 100° C. for 10 minutes; S3, using a Sc-Al-O ceramic target to prepare a 100 nm thick Sc-Al-O gate dielectric film on a film substrate by a magnetron sputtering method, wherein the Sc / Al molar ratio of the Sc-Al-O ceramic target is in the range of 0.8 to 1.2; S4. Annealing the prepared Sc-Al-O film in a tube furnace under air or oxygen conditions at 300° C. to 500° C. for 0.5 h to 2 h to obtain a dense gate dielectric material.

2. The method for preparing a scandium aluminum oxide high-k gate dielectric film according to claim 1, characterized in that: In step S3, the molar ratio of Sc / Al is preferably 1, denoted as ScAlO x The specific deposition conditions are local vacuum 5×10 -4 Pa, DC sputtering power 100W~160W, working gas pressure 0.3Pa~0.6Pa, sputtering atmosphere Ar / O2=50 / 0sccm~25sccm / 25sccm.

3. The method for preparing a scandium aluminum oxide high-k gate dielectric film according to claim 1, characterized in that: The ScAlO obtained in step S4 is also included x The electrical properties of the materials are tested. Includes the following: S5. In order to directly test the electrical properties of the gate dielectric material, a 100 nm thick and patterned metal Al layer is deposited on the above film as an electrode by magnetron sputtering combined with a shadow mask method.

4. The method for preparing a scandium aluminum oxide high-k gate dielectric film according to claim 3, characterized in that: The deposition conditions of step S5 are: local vacuum 5×10 -4 Pa, DC sputtering power 120W, working gas pressure 0.4Pa, sputtering atmosphere is pure Ar = 50sccm.

5. The method for preparing a scandium aluminum oxide high-k gate dielectric film according to claim 1, characterized in that: The effectiveness of the ScAlOx obtained in step S4 as a TFT gate dielectric layer is tested, specifically including the following contents: S6. Obtain high-density ScAlO in step S4 x A TFT device is prepared based on the material; specifically, a patterned InGaZnO (IGZO) semiconductor film is prepared as a channel layer of the TFT device by a method of magnetron sputtering combined with a shadow mask; S7, annealing the prepared IGZO film in a tube furnace at 300° C. to 400° C. for 0.5 h to 2 h in air or oxygen conditions to obtain a channel layer material with a low defect density; S8, depositing a 100 nm thick metal Al layer as an electrode on the IGZO film by using a magnetron sputtering combined with a shadow mask method; S9. Cut the gate dielectric layer at the edge to expose the underlying Si substrate serving as the gate for subsequent device performance testing.

6. The method for preparing a scandium aluminum oxide high-k gate dielectric film according to claim 1, characterized in that: In step S6, the mass ratio of each component in the IGZO semiconductor film is In:Ga:Zn=1:1:1; the deposition conditions are: local vacuum 5×10 - 4 Pa, DC sputtering power 120W, working gas pressure 0.5Pa, sputtering atmosphere is Ar / O2=46sccm / 4sccm.

7. Use of the scandium aluminum oxide high-k gate dielectric film as claimed in any one of claims 1 to 6 in a thin film transistor.

Citation Information

Patent Citations

  • High-strength Sc composite nano oxide dispersion strengthened Fe-based alloy and preparation method thereof

    CN112593161A

  • Sputtering apparatus and method for forming thin film using the same

    KR1020150086418A

  • Field effect transistor with etched-back gate dielectric

    US20050127417A1

  • An interference coating or its part consisting layers with different porosity

    US20190169739A1

  • Metal oxide thin film transistors with controlled hydrogen

    WO2018125140A1